2014
DOI: 10.1055/s-0034-1387925
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Ultrasound versus Computed Tomography for the Postoperative Follow-Up of Endovascular Abdominal Aortic Aneurysm Repair. Where Do We Stand Now?

Abstract: In the last decade, endovascular aneurysm repair (EVAR) has rapidly developed to be the preferred method for infrarenal abdominal aortic aneurysm repair in patients with suitable anatomy. EVAR offers the advantage of lower perioperative mortality and morbidity but carries the cost of device-related complications such as endoleak, graft migration, graft thrombosis, and structural graft failure. These complications mandate a lifelong surveillance of EVAR patients and their endografts. The purpose of this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…18 A significant increase in aneurysm size, the detection of a new endoleak or cases in which CDU is non-diagnostic because of obesity, gas or the lack of a suitable window, may also prompt further imaging with CTA for clarification. 3,12,36 A survey conducted in 2010 among the 41 clinical centres enrolled in the UK EVAR trial 1 47 showed that 12 out of 41 centres used CTA as the primary surveillance modality, 14 out of 41 centres used CDU as the primary surveillance modality and 15 out of 41 centres used a combination of CTA and CDU. Similarly, the recently published 15-year follow-up of the UK EVAR trial 1 48 demonstrated a shift in contemporary practice towards CDU.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…18 A significant increase in aneurysm size, the detection of a new endoleak or cases in which CDU is non-diagnostic because of obesity, gas or the lack of a suitable window, may also prompt further imaging with CTA for clarification. 3,12,36 A survey conducted in 2010 among the 41 clinical centres enrolled in the UK EVAR trial 1 47 showed that 12 out of 41 centres used CTA as the primary surveillance modality, 14 out of 41 centres used CDU as the primary surveillance modality and 15 out of 41 centres used a combination of CTA and CDU. Similarly, the recently published 15-year follow-up of the UK EVAR trial 1 48 demonstrated a shift in contemporary practice towards CDU.…”
Section: Discussionmentioning
confidence: 99%
“…The literature searches for the clinical effectiveness review were sufficiently broad that they retrieved nine relevant diagnostic test accuracy reviews. 3,62,[127][128][129][130][131][132][133] Therefore, specific searching to identify additional reviews was more focused but included appropriate subject headings and text word terms. To combine the search facets for endovascular aneurysm repair, the imaging modalities under consideration and diagnostic reviews, MEDLINE and EMBASE were searched from 1996 until March 2016, whereas the CDSR and DARE were searched on 29 March 2016 without date restrictions.…”
Section: Identification Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations